2020
DOI: 10.1007/s00415-020-10067-3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of neurological symptoms and complications of COVID-19

Abstract: Objective To study the frequency of neurological symptoms and complications in COVID-19 patients in a systematic review of the literature. Methods Relevant studies were identified through electronic explorations of PubMed, medRxiv, and bioRxiv. Besides, three Chinese databases were searched. A snowballing method searching the bibliographies of the retrieved references was applied to identify potentially relevant articles. Articles published within 1 year prior to April 20th, 2020, were screened with no languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
213
0
27

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(241 citation statements)
references
References 62 publications
(99 reference statements)
1
213
0
27
Order By: Relevance
“…A subset of COVID-19 patients present with neurological symptoms (Mao et al, 2020), including headaches, dizziness, and defects in smell and taste reported in 12-60% of patients (Chen et al, 2020). COVID-19 has been associated with acute disseminated encephalomyelitis (ADEM) (Pilotto et al, 2020;Zhang et al, 2020), mid-and long-term sequels including classical Guillain-Barré syndrome (Toscano et al, 2020;Zhao et al, 2020a), and COVID-19-associated delirium (McLoughlin et al, 2020).…”
Section: Infection Of Neurons By Sars-cov-2 In Vivo and In Vitromentioning
confidence: 99%
“…A subset of COVID-19 patients present with neurological symptoms (Mao et al, 2020), including headaches, dizziness, and defects in smell and taste reported in 12-60% of patients (Chen et al, 2020). COVID-19 has been associated with acute disseminated encephalomyelitis (ADEM) (Pilotto et al, 2020;Zhang et al, 2020), mid-and long-term sequels including classical Guillain-Barré syndrome (Toscano et al, 2020;Zhao et al, 2020a), and COVID-19-associated delirium (McLoughlin et al, 2020).…”
Section: Infection Of Neurons By Sars-cov-2 In Vivo and In Vitromentioning
confidence: 99%
“…8 SARS-CoV-2 is neurotropic and neurologic symptoms are more prevalent in patient with severe disease. 9 These numerous aetiologies for GI symptoms make it difficult to distinguish those that actually indicate disease progression. Our understanding of the virus is still limited; assessments of the long-term effects of COVID-19, particularly in patients with severe disease, are needed.…”
Section: First Sars-cov-2 May Directly Invade Gastrointestinal Cellsmentioning
confidence: 99%
“… Die am häufigsten berichteten Symptome sind Kopfschmerzen, Schwindel, Verlust von Geruchs- und/oder Geschmackssinn und eine qualitative Bewusstseinsstörung . Bei intensivpflichtigen Patienten, die an CoVID-19 erkrankt sind, treten Myoklonien, Okulomotorikstörungen, epileptische Anfälle , aber auch Dystonien auf [ 1 3 ]. Das häufigste dieser Symptome ist der Geruchs- und/oder Geschmacksverlust (Anosmie, Ageusie), der von ca.…”
Section: Prüfungsfragenunclassified
“… Das häufigste dieser Symptome ist der Geruchs- und/oder Geschmacksverlust (Anosmie, Ageusie), der von ca. 60–80 % der Betroffenen berichtet wird [ 1 , 2 ]. …”
Section: Prüfungsfragenunclassified
See 1 more Smart Citation